2021
DOI: 10.3390/molecules26030606
|View full text |Cite
|
Sign up to set email alerts
|

JAK2 Inhibition by Fedratinib Reduces Osteoblast Differentiation and Mineralisation of Human Mesenchymal Stem Cells

Abstract: Several signalling pathways, including the JAK/STAT signalling pathway, have been identified to regulate the differentiation of human bone marrow skeletal (mesenchymal) stem cells (hBMSCs) into bone-forming osteoblasts. Members of the JAK family mediate the intracellular signalling of various of cytokines and growth factors, leading to the regulation of cell proliferation and differentiation into bone-forming osteoblastic cells. Inhibition of JAK2 leads to decoupling of its downstream mediator, STAT3, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
(77 reference statements)
0
8
0
Order By: Relevance
“…Our above-obtained results showed that CGF promotes hBMSCs osteogenic differentiation in a co-culture system, but the underlying mechanism is not clear. Various signaling pathways have been found to regulate the osteogenic differentiation of hBMSCs, including Notch signaling, Wnt/β-catenin, MAPK singaling,TGFβ, BMP-Smad singaling, Jak-STAT signaling, and Hedgehog signaling( AlMuraikhi et al, 2021 ; Pengjam et al, 2016 .). Therefore, we performed RNA-Seq and KEGG pathway analysis to further study the underlying mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Our above-obtained results showed that CGF promotes hBMSCs osteogenic differentiation in a co-culture system, but the underlying mechanism is not clear. Various signaling pathways have been found to regulate the osteogenic differentiation of hBMSCs, including Notch signaling, Wnt/β-catenin, MAPK singaling,TGFβ, BMP-Smad singaling, Jak-STAT signaling, and Hedgehog signaling( AlMuraikhi et al, 2021 ; Pengjam et al, 2016 .). Therefore, we performed RNA-Seq and KEGG pathway analysis to further study the underlying mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…They direct a variability of chemokines and cytokines which boost healing of degraded tissues and restoration of metabolism and inflammation. Usually, the emission of therapeutic factors enhances upon permission by inflammatory signals or apoptosis, which are encouraged by the host immune system [70].…”
Section: Graphene and Graphene Oxidementioning
confidence: 99%
“…MSCs can self-renew and differentiate into different cell types, including bone osteoblast cells [ 15 , 16 ]. The osteoblastic differentiation of human MSCs comprises complicated processes controlled by various signaling pathways, including Wnt [ 17 , 18 ], Tankyrase [ 19 ], JAK-STAT signaling [ 20 , 21 ], Hedgehog signaling [ 22 ], TGFβ [ 23 ], BMP/Smad [ 24 ], PI3K/Akt/mTOR [ 25 ], and Notch signaling [ 26 ]. However, their relative involvement on osteoblastic differentiation must be further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…However, their relative involvement on osteoblastic differentiation must be further investigated. Small-molecule inhibitors have been widely exploited as biochemical tools to help investigate the involvement of different signaling pathways in osteoblastic differentiation, which may reflect on therapeutic findings [ 19 , 20 , 21 , 22 , 26 ].…”
Section: Introductionmentioning
confidence: 99%